Training on the Application of Climate Foresight Data in Enhancing Agricultural Policy Implementation and Decision- Making in Eastern and Central Africa - Barungi, Julian; Recha, John W.M.; Demissie, Teferi Dejene (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
A paradigm shift is required in policies to make food systems sustainable. The climate foresight workshop highlights the critical role of collaborations between farmers and corporate, governmental, and entities involved in extension and training services as well as research and development. The workshop demonstrates that stakeholders (Fig. 2) at different dimensions of the climate service value chain and across different industries may collaborate to achieve shared, synergistic aims